Pengaruh Intensitas Cahaya Matahari Terhadap Perkecambahan Dan Pertumbuhan Biji Gulma (Asystasia Gangetica L) - Sitinjak, Lentina (AGROSUSTAIN, 2025)
This study aims to control the growth of Asystasia gangetica L plants and observe the effect of sunlight intensity on the germination and growth of Asystasia gangetica L plants. Asystasia gangetica L is often considered a weed that interferes with the growth of cultivated plants, including oil palm. This phenomenon is interesting to study because the growth of this weed can compete with cultivated plants. This research was conducted in the agricultural land of Santo Thomas Catholic University, Medan. North Sumatra. With an altitude of 2.5 - 37.5 meters above sea level (MDPL). This research began in August 2024 until October 2024. This research method uses a non-factorial RAK (Randomized Block Design) consisting of one treatment, namely sunlight intensity and consists of 5 levels, namely: N0: 100% light intensity, N1: 80% light intensity, N2: 60% light intensity, N3: 40% light intensity, N4: 20% light intensity with a linear model. Based on the research results, the intensity of sunlight has a significant effect on the observed parameters, namely germination at ages 1 and 2 MST, plant height at ages 2,4,6,8,10,12 MST, number of leaves at ages 2,4,6,8,10,12 MST, number of branches 4,6,8,10,12 MST, number of panicles 6,8,10,12 MST and number of tubes (capsules) 8,10,12 MST